1968
DOI: 10.3133/pp572
|View full text |Cite
|
Sign up to set email alerts
|

Geology and coal resources of the Elk Valley area, Tennessee and Kentucky

Abstract: The 240-square-mile area described in this report includes the Ivydell, Jellico 'Vest, Ketchen, and Pioneer 7lh-minute quadrangles in Scott and Campbell Counties, Tenn., and McCreary and Whitley Counties, Ky. Elk Yalle.y, the source of the area name, is centrally located.The quadrangles of this report are in the Cumberland Mountain section of the Appalachian Plate-aus province, except for the southeast co•rner of the Ivydell quadrangle which is in the Valley and Ridge province. That part of the area in the Cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Perhaps the first aspect of Pine Mountain block deformation to strike anyone looking for deformation features is the lack of them. Despite the fact that bedding dips as steeply as 70 ø in places (northwest of Powell Valley anticline, southwest end of block), outcrop-scale folding and faulting are restricted almost exclusively to within about 100 m of the major faults [Miller and Fuller, 1954;Englund, 1968;Wiltschko, 1977]. Table 1 summarizes the inferred conditions and nature of the deformation in the upper plate.…”
Section: Deformationmentioning
confidence: 98%
See 1 more Smart Citation
“…Perhaps the first aspect of Pine Mountain block deformation to strike anyone looking for deformation features is the lack of them. Despite the fact that bedding dips as steeply as 70 ø in places (northwest of Powell Valley anticline, southwest end of block), outcrop-scale folding and faulting are restricted almost exclusively to within about 100 m of the major faults [Miller and Fuller, 1954;Englund, 1968;Wiltschko, 1977]. Table 1 summarizes the inferred conditions and nature of the deformation in the upper plate.…”
Section: Deformationmentioning
confidence: 98%
“…Greater displacement of the fault produced a broader anticline with the same structural relief [Rich, 1934]. Powell Valley anticline narrows to the northeast, and Englund [1968,1971] and Harris [1970] have also shown that displacement decreases from 18 to 7 km in that direction [Englund, 1968, Figure 19, 1971Harris, 1970, p. 163]. The Pine Mountain block has both rotational and translational components to its movement.…”
Section: Kinematicsmentioning
confidence: 99%
“…On the basis of their common stratigraphic position with respect to the Dingess Shale Member and certain extensively mined coal beds, the Winifrede has been correlated with the Magoffin Member of the Breathitt Formation in Kentucky by Wanless (1939, p. 53), Outerbridge (1976), and Blake et al (1989). The Winifrede Member and its correlatives are probably among the most widely recognized and mapped Middle Pennsylvanian units in the central part of the Appalachian basin, extending from east-central West Virginia to Scott County, Tennessee (Englund, 1968). In Kentucky, this horizon was earlier referred to as the "Fossil Limestone" by Wanless (1946).…”
Section: Winifrede Shale Membermentioning
confidence: 98%
“…Although the Fire Clay tonstein has been traced from West Virginia across Virginia and Kentucky to Tennessee, both on the Cumberland overthrust sheet and in the autochthonous portion of the basin northwest of the overthrust sheet (Wanless, 1946), there is an area that is stratigraphically and structurally isolated at the southwestern end of the Cumberland overthrust sheet where the identity of the tonstein has been questioned. Rice (1984) determined that the stratigraphic position of the Fire Clay tonstein in that area was in the Walnut Mountain coal bed, about 80 m higher in the Pennsylvanian section than had been previously indicated by Glenn (1925) and Englund (1968). We collected sample RI of the tonstein in Glenn's (1925) type Walnut Mountain coal bed on Walnut Mountain in Campbell county, Tennessee, for 40 Ar/ 39 Ar age spectrum dating and for a comparison of its phenocryst mineralogy with that of other samples of the Fire Clay tonstein dated in this study.…”
Section: Introductionmentioning
confidence: 99%